Evaluation of Ethanol Extract of Red Algae (Kappaphycus Alvarezii Doty): Total Phenolic and Flavonoid Content - . S, Aminah; Arianto, Anayanti; Dalimunthe, Aminah (Talenta Publisher, 2022)
This study aims to determine the characterization of red algae simplicia and the amount of yield obtained from the manufacture of red algae ethanol extract using the soxhletation method. Red algae were taken from Banggai Islands Regency, South Sulawesi and processed into dry simplicia and characterized by macroscopic examination, determination of water content, content of water soluble extract and ethanol, total ash content and acid insoluble ash content. Simplicia was extracted using 96% ethanol solvent by soxhletation method and calculated the amount of yield obtained. Macroscopic observation of red algae simplicia obtained a brown coarse powder accompanied by a distinctive taste and odor. Determination of the water content of simplicia obtained 7.21%, water soluble extract content 31.54%, ethanol soluble extract content 17.27%, total ash content 33, 96% and 11.42% acid insoluble ash content. The ethanolic extract of red algae using the soxhletation method was obtained as much as 68.92 grams with a total extract yield of 13.78%. Based on the results of the study, it can be concluded that the simplicia characterization of red algae meets the requirements and has a large extract yield.